Oracle E-Business Suite R12 core development and extension cookbook : over 60 recipes to develop core extensions in Oracle E-Business Suite R12 /: over 60 recipes to develop core extensions in Oracle E-Business Suite R12. (2012) - Unknown
No abstract available